Capitalism and Culture in Peru's Neoliberal Process (1990–2013): Notes from an Ayacucho Community. (September 2019) - Cepeda-Caceres, Mario R.
Peruvian society underwent a profound transformation following the crisis of the 1980s and the structural reforms implemented in the 1990s. New paradigms were created in rural areas that connected previous discourses on local identity with market dynamics through tourism. The campesino community of Lucanas went from successful management of the vicuña to an economy that pursued market performance practices by adopting a neoliberal paradigm. A distinctive way of living with the structural changes, here called "culturally appropriated capitalism, " produced a new national consciousness—a new way of seeing and relating to the world, from the economic to the cultural. Luego de la crisis peruana de la década de 1980 y las reformas estructurales implementadas en la década de 1990, la sociedad peruana sufrió una transformación profunda. En el ámbito rural, se crearon nuevos paradigmas que enlazaban antiguos discursos sobre la identidad local con las dinámicas del mercado a través del turismo. La Comunidad Campesina de Lucanas pasó de tener éxito en el manejo de la vicuña a una economía que apuesta por las prácticas performativas del mercado adoptando el paradigma neoliberal. Una forma particular de vivir las reformas estructurales, aquí llamado "capitalismo achorado", produjo una nueva conciencia nacional—una nueva manera de ver y relacionarse con el mundo, desde lo económico hacia lo cultural.